Cooling of concentrated photovoltaic cells - a review and the perspective of pulsating flow cooling - Ibrahim, Khalifa Aliyu; Luk, Patrick Chi-Kwong; Luo, Zhenhua (MDPI, 2023)
This article presents a review to provide up-to-date research findings on concentrated photovoltaic (CPV) cooling, explore the key challenges and opportunities, and discuss the limitations. In addition, it provides a vision of a possible future trend and a glimpse of a promising novel approach to CPV cooling based on pulsating flow, in contrast to existing cooling methods. Non-concentrated photovoltaics (PV) have modest efficiency of up to around 20% because they utilise only a narrow spectrum of solar irradiation for electricity conversion. Therefore, recent advances employed multi-junction PV or CPV to widen the irradiation spectrum for conversion. CPV systems concentrate solar irradiation on the cell’s surface, producing high solar flux and temperature. The efficient cooling of CPV cells is critical to avoid thermal degradation and ensure optimal performance. Studies have shown that pulsating flow can enhance heat transfer in various engineering applications. The advantage of pulsating flow over steady flow is that it can create additional turbulence and mixing in the fluid, resulting in a higher heat transfer coefficient. Simulation results with experimental validation demonstrate the enhancement of this new cooling approach for future CPV systems. The use of pulsating flow in CPV cooling has shown promising results in improving heat transfer and reducing temperature gradients.
Keywords: concentrated solar cell; solar energy; CPV cooling mechanism; electrical and thermal efficiency; high heat flux dissipation; heat transfer enhancement